Examining Personalities and Behavioural Syndromes in the Burying Beetle, Nicrophorus vespilloides Herbst, 1783 - Pavol Prokop; Jozef Balcečík; Rudolf Masarovič; Zuzana Provazník (Ecology and Evolution, 2025)
ABSTRACT Animal personality encompasses behavioral traits that can vary between individuals while remaining stable over time for each individual. These traits often correlate with each other and form behavioral syndromes. In our study, we investigated the personalities and behavioral syndromes of the burying beetle Nicrophorus vespilloides, which defends and prepares carcasses as food for its offspring. In the laboratory, we repeatedly examined overall mobility, explorative behavior, duration of stridulation, and tonic immobility in the same individuals. Overall mobility and stridulation exhibited moderate repeatability in both sexes. Tonic immobility (TI) was more repeatable in females than in males, whereas exploratory behavior did not show repeatability in either sex. Results showed that males remained in tonic immobility for significantly longer periods than females. Contrary to our expectations, females exhibited greater exploratory behavior than males. The duration of stridulation was similar between the sexes, but individuals with poorer body conditions stridulated for a longer time than individuals with better physical conditions. Stridulation is triggered by simulated predatory attacks, suggesting that it may serve as a defense mechanism against predators. We conclude that the functional significance of personality traits in N. vespilloides warrants further investigation in the context of their natural predators and conspecifics.